Designing Sorting Networks A New Paradigm - Al-Haj Baddar, Sherenaz W.; Batcher, Kenneth E.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Designing Sorting Networks: A New Paradigm provides an in-depth guide to maximizing the efficiency of sorting networks, and uses 0/1 cases, partially ordered sets and Haase diagrams to closely analyze their behavior in an easy, intuitive manner. This book also outlines new ideas and techniques for designing faster sorting networks using Sortnet, and illustrates how these techniques were used to design faster 12-key and 18-key sorting networks through a series of case studies. Finally, it examines and explains the mysterious behavior exhibited by the fastest-known 9-step 16-key network. Designing Sorting Networks: A New Paradigm is intended for advanced-level students, researchers and practitioners as a reference book. Academics in the fields of computer science, engineering and mathematics will also find this book invaluable.
Preface -- Early History -- Software Implementations -- POSETS -- The 0/1-Principle -- A 16-Key Sorting Network -- The Sortnet Program -- Divide & Conquer -- Counting Strangers -- Finding Better Networks -- Lattice Theory -- The AKS Sorting Network -- Ideas For Faster Networks -- BOOL(N) -- Sorting Networks For Large N -- Another Way Of Handling Strangers -- Thoughts On Minimizing Strangers -- Case Studies -- Appendix I: Proofs of Theorems -- Index.
Keywords: Computer science; Data structures (Computer science).; Computer Science; Data Structures; Arithmetic and Logic Structures; Models and Principles